ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PEMUNGUTAN PAJAK DAERAH ( Studi pada Dinas Pendapatan Daerah Kabupaten Tulungagung ) - Saputra, Andys Dwi (Jurnal Mahasiswa Perpajakan, 2014)
Local tax is contributing the highest revenue to Local Genuine Income (PAD). The government attempts to increase the effectiveness of local tax collection to improve PAD, especially through tax post. There are factors influencing the effectiveness of local tax revenue. The objective of research is to understand the influence of inflation rate, population rate, and Gross Regional Domestic Product (PDRB) on local tax revenue in Tulungangung District in period 2008-2012. Data type is secondary data (time series) for period 2008-2012 obtained from the Official of Local Revenue and the Statistic Bureau (BPS) in Tulungagung District. Literature study is conducted to support data collection. Result of research indicates that the effectiveness of local tax collection in Tulungangung District in period 2008-2012 is entirely very effective. Of all three variables observed, which are inflation rate, population rate and PDRB, one with the most dominant influence on local tax revenue is population rate. Based these results, it may be suggested that the local government of Tulungangung District, especially the Official of Local Revenue of Tulungangung District, in determining local tax shall firstly socialize the importance of tax for the development such that taxpayer will be aware of paying tax in exchange for their welfare. Keywords: Local Tax, Inflation Rate, Population Rate and PDRB